Gut microbiota in chronic obstructive pulmonary disease varies by CT-verified emphysema status - Anders Ørskov Rotevatn; Tomas Mikal Eagan; Solveig Tangedal; Gunnar Reksten Husebø; Kristoffer Ostridge; Rune Nielsen (European Clinical Respiratory Journal)
Background and aim The association of the gut microbiota to chronic obstructive pulmonary disease (COPD) phenotypes is underexplored. We aimed to compare stool samples from patients with COPD and subjects without COPD and relate findings to emphysema status, exacerbation rate, blood eosinophil levels, symptom score, and lung function.Methods We report findings from a single-centre case–control study with 62 current and former smoking patients with COPD and 49 subjects without COPD. DNA was extracted from stool samples, and the V3V4-region of the bacterial 16S-rRNA gene was sequenced. Emphysema was defined based on thoracic computed tomography (CT thorax) low attenuating areas ≥/<10% at threshold -950 and -910 hounsfield units, respectively. Differential abundance of taxa was evaluated using Analysis of Composition of Microbes with Bias Correction (ANCOM-BC). Beta diversity was compared using a distance-based permanova-test.Results The genus Veillonella was decreased and a genus belonging to class Clostridia was increased in COPD compared with controls without COPD. The composition of microbes (beta diversity) differed in emphysema compared to controls, and 27 genera were differentially abundant in emphysema vs. controls. Nine of these genera belonged to the family Lachnospiraceae. Lung function, blood counts and COPD assessment test score correlated with several genera’s relative abundance. Of the genera showing significant correlation to lung function, nine belonged to the family Lachnospiraceae.Conclusion The gut microbiota in COPD differs from that in healthy individuals, even more so in emphysema. In particular, future studies should look into the mechanisms and therapeutic potential of dysbiosis affecting the family Lachnospiraceae.